Swimming against the tide: the changing functions and status of chaplains in the Israel Defense Force. Issue 1 (2nd January 2016) - Cohen, Stuart; Kampinsky, Aaron; Rosman-Stollman, Elisheva
ABSTRACT: This article describes and analyses the changes that have occurred in the services performed by chaplains in the Israel Defense Force (IDF) – the only military in the world that consists almost entirely of Jews. Essentially, we argue, the shift has been one of focus. For many years, IDF chaplains primarily (albeit never exclusively) concerned themselves with providing religious services to the minority of personnel who observed Orthodox Jewish rituals. 'Outreach' programmes, targeted at the secular Jewish majority, were secondary. Recently, however, the IDF rabbinate has undergone a process of 'role expansion', emphasising the provision of counselling and guidance to the entire Jewish complement, especially in combat units. In the second part of the article, we analyse the possible reasons for that development: demographic and cultural trends in Israeli society; the prominence of counter-insurgency missions in the IDF's operational agenda; and the personalities of recent chief chaplains. Finally, we address the possible implications of this shift, asking whether the intra-organisational frictions that it generates, especially with the Education Corps, portends a battle for the soul of the IDF.